Investigating the Copper Phytotoxicity on in-vitro Culture of Musa acuminata cv. ‘Bantala’ - Bandita Deo; Preetam Kumar Nayak (Cutting-edge Research in Agricultural Sciences Vol. 13, 2021)
The present study aimed to investigate the effect of different concentration of copper on growth and development of MUSA ACUMINATA cv. Bantala grown IN VITRO. Copper (Cu) is an essential transition metal that is involved in many physiological processes in plants, because it can exist in multiple oxidation states in vitro. The results showed that 1.0 µM copper stimulated root induction, elongation and shoot growth when compared with the control (0.1 µM copper). In addition, higher level of copper (100 µM) has toxic effect on banana leaves with regard to stunted growth, curling leaf and complete inhibition of root formation. Copper exposure increased photosynthetic pigment contents, decreased carbohydrates and protein contents at 100 µM of copper. This investigation will help to estimate the copper tolerant plants for phyoremediation programme.